NURSING CARE TO CLIENTS WITH PARKINSON'S DISEASE IN PRIMARY CARE HEALTH - Barbara Juliana Konig Küster; Luiz Anildo Anacleto da Silva; Marinês Tambara Leite; Marta Cocco da Costa (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976929074 Aim: to analyze the actions performed by nurses care users with Parkinson's disease who access basic health care. Method: qualitative, exploratory and descriptive search with thematic analysis. The research subjects were nine nurses in Basic Healthcare Units. Results: The results show that there is no record of users with this disease in the area covered by the work of nurses, may compromise nursing care to individuals with Parkinson's disease. Final Considerations: family participation is important and should be addressed and integrated into the planning of nursing care to individuals who have Parkinson's disease.